Endovascular Treatment of Right Heart Masses Utilizing the AngioVac System: A 6-Year Single-Center Observational Study. (31st October 2021) - Katapadi, Aashish; Richards, Lauren; Fischer, William; Allaqaband, Suhail Q.; Bajwa, Tanvir; Jan, M. Fuad
Abstract : Objective . To describe our institution's experience with the AngioVac system. Background . Intracardiac and intravascular masses previously required surgical excision, but now, there are a number of minimally invasive options. With the advent of vacuum aspiration, more specifically the AngioVac System (AngioDynamics, NY, USA), there exists a system with both low mortality and minor complications. However, the number of retrospective studies remains limited. Outcome data for high-risk patients are also limited. Methods . Data were collected and analyzed in patients who underwent AngioVac therapy at our tertiary care center from January 2014 to December 2020. Results . Our results demonstrated a 93.3% intraoperative success rate and a 100% intraoperative survival rate. However, a number of complications, including but not limited to hematomas, anemia, and hypotension, occurred, as described below. Conclusions . Our experiences demonstrated good outcomes and continue to support the usefulness of the AngioVac System. The data also support the use of AngioVac as a treatment option for the debulking or removal of right heart masses in critically ill patients.